Interrelations between service quality, customer satisfaction, and purchase intention in fast food restaurants : A study on generation Y in Kuala Lumpur Malaysia / Atikah Saifuddin - Saifuddin, Atikah (2012)
In any business, the service quality and customer satisfaction are the two most important key marketing strategies for competitive differentiation and customer retention. An understanding of this issue will help business to become more successful. Due to the competition in the business, customer satisfaction measurement has become common practice in the fast food restaurants throughout the world with the aim of assessing the quality of existing management practice and suggesting the direction for improvement. The aims of this study are to examine the most influence key determinants of customer satisfaction towards service quality level and to identify the interrelations between customer satisfaction and customer purchase intention in fast food restaurants in Kuala Lumpur, a study on generation Y. For generation Y, no study has yet investigated the above mentioned interelationship. The purpose of this study is to fill this gap. A questionnaire survey which is designed according to the SERVQUAL model was used to measure service quality. Other conceptually related variables were included in this research, such as consumer purchase intention, overall service quality and overall satisfaction. The sample sizes of 100 were drawn. The result reveals that all the service quality are positively related to customer satisfaction and customer satisfaction is positively related to customer purchase intention in the fast food restaurants in Kuala Lumpur, a study on generation Y. Responsiveness demonstrates the highest positive linear correlation with customer satisfaction and reliability shows the weak positive linear correlation with customer satisfaction. This study suggests that SERVQUAL is a suitable instrument for measuring the fast food restaurants in the generation Y context. Therefore, fast food restaurants managers can use this instrument to assess the fast food restaurants service quality in Kuala Lumpur, Malaysia